Field Evaluation of Manure-Based Amendments and Biological Control Agents’ Influence on Root Lesion Nematodes in Potato - Luisa M. Parrado; Emilie Cole; Marisol Quintanilla (PhytoFrontiers)
Potato yields are significantly impacted by soilborne diseases such as the root-lesion nematode, Pratylenchus penetrans. Traditional management strategies involve soil fumigation with broad-spectrum pesticides, such as metam sodium, and postplanting applications of nonfumigant nematicides, including oxamyl and fluopyram. In Michigan, approximately 35% of potato hectares are treated with metam sodium, and 50 to 60% of potato hectares are amended with customized manure-based composts. Considering the critical impact of this nematode on the potato industry, along with potential future restrictions on chemical use due to environmental concerns and the growing adoption of organic soil amendments by Michigan potato growers, it is essential to validate manure-based amendments as an alternative management strategy for P. penetrans. To explore this, two field trials were conducted in 2020 and 2021 to assess the impact of manure-based amendments, biological control agents, oxamyl, and their combinations on P. penetrans. This study found that applying raw poultry manure at a rate of 3.08 tons ha−1, either alone or combined with a single application of oxamyl at 2.5 liters ha−1, effectively maintained low P. penetrans populations in both soil and roots. Additionally, Compost A and poultry manure increased potato yields. Moreover, the combined application of manure-based amendments and Purpureocillium lilacinum (MeloCon) showed varying efficacy depending on the amendment used. Our studies provide the necessary evidence that validates the efficacy of these management practices to reduce P. penetrans populations and to enhance potato yields. [Figure: see text] Copyright © 2025 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.